2012
DOI: 10.5009/gnl.2012.6.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hemorrhagic Peptic Ulcers in Patients Receiving Antithrombotic/Nonsteroidal Antiinflammatory Drug Therapy

Abstract: Background/AimsAntithrombotic/nonsteroidal antiinflammatory drug (NSAID) therapies increase the incidence of upper gastrointestinal bleeding. The features of hemorrhagic peptic ulcer disease in patients receiving antithrombotic/NSAID therapies were investigated.MethodsWe investigated the medical records of 485 consecutive patients who underwent esophagogastroduodenoscopy and were diagnosed with hemorrhagic gastroduodenal ulcers. The patients treated with antithrombotic agents/NSAIDs were categorized as the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Some studies have reported that patients with peptic ulcers treated with antithrombotics are at great risk of bleeding severely enough to require transfusion . In the present study, mean hemoglobin levels on admission were significantly lower in group A than in group NA; however, the transfusion volumes were significantly lower in group A than in group NA.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Some studies have reported that patients with peptic ulcers treated with antithrombotics are at great risk of bleeding severely enough to require transfusion . In the present study, mean hemoglobin levels on admission were significantly lower in group A than in group NA; however, the transfusion volumes were significantly lower in group A than in group NA.…”
Section: Discussioncontrasting
confidence: 67%
“…2,3 Antithrombotic agents, including low-dose aspirin, antiplatelet drugs, and anticoagulants, are considered to increase the risk of UGIB. 4 Although an increased incidence of UGIB during administration of antithrombotic therapies has been extensively described, 5 the precise characteristics of UGIB associated with antithrombotic therapies are less understood than those of UGIB unassociated with antithrombotic therapies. Additionally, many endoscopists have had more opportunities to carry out diagnostic and therapeutic endoscopy on patients receiving antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that this result may be caused by the increased concomitant use of antithrombotic agents because of the increase in elderly population [1]. Recently, dual antiplatelet therapies with combinations of LDA and another antiplatelet have become a standard therapy in patients with coronary artery diseases treated with drug-eluting stents [19]. Such combined antithrombotic therapies further increase the threat of PUB compared with antiplatelet monotherapies [14].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of patients are being given antithrombotic agents for vascular protection [19]. A recent meta-analysis showed that LDA increased the risk for gastrointestinal bleeding and the risk increased with accompanying use of clopidogrel and anticoagulant therapies [20].…”
Section: Discussionmentioning
confidence: 99%
“…10 An increased incidence of UGIB during the administration of antithrombotic therapies has been extensively described, providing endoscopists with more instances to perform emergency endoscopy procedures on patients who are taking antithrombotic agents. 13,14 Emergency endoscopic hemostasis has proven bene cial in all cases of UGIB. [15][16][17][18] In terms of promptness, urgent endoscopy performed within 24 hours of UGIB has been shown to diminish the likelihood of mortality and surgical intervention in high-risk UGIB cases.…”
Section: Introductionmentioning
confidence: 99%